1984
DOI: 10.3382/ps.0631935
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hot Boning Broiler Breast Muscle on pH Decline and Toughening

Abstract: Studies were conducted to determine the relationship of the postmortem pH decline of hot-boned broiler breast muscle (Pectoralis major) to the increased toughness often associated with hot boning. A total of 68 broilers were New York dressed, and trials were conducted to compare breast halves either hot boned at 0, 15, 30, 60, 120, or 240 min postmortem with the other (control) half allowed to remain on the carcass for 24 hr prior to removal. The pH values were taken on each bird at time of kill, time of excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 6 publications
8
42
0
3
Order By: Relevance
“…pH values of breast muscle were significantly decreased from 6.32 at 0.5 h PM to 5.82 after 6 h PM, whereas there were no significant differences among at 6, 12, and 24 h PM in general agreement with previous study (Stewart and Fletcher, 1984) where reported decreases in pH values tended to level off at 5.9 after 4 h or before. Early studies by De Fremery and Pool (1960) revealed that the rigor mortis of chicken muscle was completed at 6 h before PM and achieved ultimate pH.…”
Section: Resultssupporting
confidence: 82%
“…pH values of breast muscle were significantly decreased from 6.32 at 0.5 h PM to 5.82 after 6 h PM, whereas there were no significant differences among at 6, 12, and 24 h PM in general agreement with previous study (Stewart and Fletcher, 1984) where reported decreases in pH values tended to level off at 5.9 after 4 h or before. Early studies by De Fremery and Pool (1960) revealed that the rigor mortis of chicken muscle was completed at 6 h before PM and achieved ultimate pH.…”
Section: Resultssupporting
confidence: 82%
“…The change in muscle tenderness may correlate with that of pH value. A similar relationship between pH and tenderness has been previously reported (Stewart et al, 1984;Cavitt et al, 2005); however, the ranges of pH and tenderness values in previous studies have been representative of multiple deboning times rather than one. Stewart et al (1984) suggested that the relationship of pH (at time of deboning) and tenderness is not cause-effect but rather a parallel relationship in which pH is an indicator of rigor mortis development rather than directly affecting meat tenderness.…”
Section: The Effect Of Scesc On Carcass and Meat Quality Of Aa Broilersmentioning
confidence: 67%
“…times. Although not indicated in the table, the 0-h mean was significantly (P < .05) greater than the samples collected from control carcasses at 1 h. This represents the normal post-mortem pH decline that occurs as a result of lactic acid accumulation and has been previously reported (Stewart et al, 1984). At 1 h post-mortem, the Pectoralis pH was significantly higher in the control muscles than in the two rigor-acceleration treatments, which were not different from each other.…”
Section: Methodsmentioning
confidence: 86%
“…The first is rigor mortis development, in which post-mortem muscle cell metabolism gradually shifts from aerobic to anaerobic pathways, adenosine triphosphate (ATP) is depleted, and actomyosin is formed (Hamm, 1982). In broiler breast muscle this process requires 4 h and if meat is deboned prior to this time it is toughened (Stewart et al, 1984;Lyon et al, 1985;Dawson et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation